Perencanaan dan Perancangan Resort di Kabupaten Jembrana: Bahasa Indonesia - Kadek Hendrik Valentino; I Nyoman Nuri Arthana; I Kadek Merta Wijaya (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Jembrana Regency has natural beauty and beautiful beaches so that it can attract tourists to visit. The development of this area can increase if it is developed potentially, resorts are the right choice to be built in this area, because resorts have facilities that can support tourists. The purpose of this resort is to provide comfort by prioritizing environmental friendliness, reducing air conditioner energy use, with efforts to solve design problems in order to provide the best solution. This resort is expected to be able to overcome existing design problems. In planning and designing this resort will have good benefits for tourism in the Jembrana area, especially in Perancak Beach, the facilities are arranged based on zoning and circulation flow. With the construction of this resort, it is hoped that it will be able to lift, enliven, facilitate the progress of tourism in the Perancak Beach area.